Pengolahan Bahan Organik Menjadi Produk Makanan Kucing “MiMeow” - Wirren Chang; Edy Yulianto Putra; Agnes Doraresta Khatarina Tokan; Delfina Muthia Sabella; Dewi Dewi; Mardiana Ng; Serina Serina (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Stray cats are usually easily infected with disease because they don't have owners to take care of them, wild cats generally take food in the trash which is definitely not suitable for consumption because it's not only dirty but the food in the trash doesn't contain enough nutrients. This is what made the researchers come up with the idea to produce a healthy and nutritious food for wild cats and domestic cats named